Mosquitex, a new tool for capturing Aedes (Stegomyia) aegypti (Linnaeus, 1762) (Diptera: Culicidae) - Guimarães, Cyro (2024)
The species Aedes (Stegomyia) aegypti (Linnaeus, 1762) (Diptera: Culicidae) is of great importance for human health, as it is responsible for the transmission of viruses that can cause dengue, chikungunya, zika and urban yellow fever. The proposal of this study is to test the efficiency of a new trap model in capturing and trapping Ae. aegypti based on favoring the insect's ecology. This trap model was analyzed regarding the attractiveness for egg-laying, and the trapping of larvae and consequently the adults. The tests were carried out using white traps (original version) and black traps (adapted from the original), both in field and laboratory conditions. In the field, the black traps showed 100% effectiveness compared to white traps, showing more positive results for the attractiveness of Ae. aegypti mosquito and adult imprisonment. According to the results for this trap model, from both test in the field and in the laboratory, it was concluded that this new product is effective in capturing Ae. aegypti and it guarantees mosquito trapping safety, also low-cost production, practicality, logistics and possibility of its use by the local population. After the validation and effectiveness of the trap “drinking-fountain like”, the definitive trap called Mosquitex was developed, which is brand new for this mosquito, with patent registration INPI - BR2020190112226 - 2019, and with the possibility of assisting in the control and monitoring of Ae. aegypti in urban areas.